Mediation and third party interventions in collective conflicts in organizations - Pinheiro, A. (2018)
This open access book opens up the black box of mediation in collective conflicts through the analyses and comparisons of various systems. Mediation and related third party interventions such as conciliation and facilitation are discussed as effective prevention and regulation tools for different types of collective labor conflicts. These interventions fit in a new developed five-phase model of collective conflicts in organizations, going from capacity building in latent conflicts, through conciliation, mediation and arbitration in escalating phases, to rebuilding of trust after hot conflicts. The authors promote understanding and discussion with regards to labor mediation systems, presenting comparative research on the perspectives of mediators and users of mediation. This book describes and analyses laws, regulations and practices of mediation in seventeen countries, with a relative strong emphasis on Europe. Part 1 presents theoretical frameworks on conciliation and mediation in collective labor conflicts. Part 2 presents regulations and practices in 12 European countries: Belgium, Denmark, Estonia, France, Italy, Poland, Portugal, Spain, The Netherlands, and the United Kingdom. Part 3 discusses mediation in these collective conflicts in Australia, China, India, South Africa and the USA. Part 4 offers conclusions and ways forward. This book offers analyses, good practices and developments for third party intervention in collective labor conflicts in global and local changing environments. This book is a must-read for policy makers, , social partners at different levels, as well as scholars and practitioners in industrial relations, human resources management and conflict management, particularly conciliators and mediators.